Utiliser la polysémie de la résilience pour comprendre les différentes approches du risque et leur possible articulation - Magali Reghezza-Zitt (EchoGéo)
Resilience is a fashionable buzzword. But the polysemy of the concept may weaken his relevance. This paper aims at demonstrating two points. First, this polysemy is obviously linked with a multidisciplinary construction. However we assume that the polysemy can be explained in another way: one single world expresses two different paradigms. Those paradigms may have some things in common, but they cannot be merged. Secondly, we will show that it is possible to solve the contradictions created by that polysemy, if we reconsider the different meanings of resilience in relation with each paradigm. Resilience is thus a reflexive tool, which allows a better understanding of the risk and hazard research fields.